Radical evolution : the promise and peril of enhancing our minds, our bodies--and what it means to be human - Garreau, Joel. (New York : Doubleday, 2005)
Journalist Garreau shows us that we are at an inflection point in history: we are engineering the next stage of human evolution. Through advances in genetics, robotics, information and nanotechnologies, we are altering our minds, our memories, our metabolisms, our personalities, our progeny--and perhaps our very souls. Taking us behind the scenes, Garreau reveals that superpowers--from revved-up reflexes and speed, to enhanced mental acuity and memory capabilities--already exist, or are in development in labs and research facilities. These enhancements will soon become part of our everyday lives. Will technology's promise to make us smarter, vanquish illness and extend our lives be the answer to our prayers? Or will unrestrained technology bring about the ultimate destruction of our species? With the insights of gifted thinkers and scientists who are making science fiction a reality, Garreau explores how these developments, in our lifetime, will affect everything from the way we date to the way we work, from how we think and act to how we fall in love.--From publisher description.
Includes bibliographical references (p. [283]-350) and index.
Keywords: Human evolution; Technological innovations; Bioengineering; Technology -- Risk assessment